2023
DOI: 10.2478/bhk-2023-0010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute taurine consumption on single bout of muscular endurance resistance exercise performance and recovery in resistance trained young male adults

Abstract: Study aim: This study investigated the effect of taurine supplementation on exercise performance and recovery from resistance exercise. The study was conducted with a cross-over design in a double-blind manner. Material and methods: Ten resistance trained males (age 21.4 ± 2.01 years; BMI: 23.6 ± 2.5 kg/m²) ingested either a taurine (0.1g/kg) supplement or placebo (18 mg aspartame) prior to resistance exercise. Vertical jump, flexibility, balance, systolic blood pressure, dias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In healthy subjects, benefits of Tau supplementation on aerobic and anaerobic performance, muscle damage, metabolic stress, and recovery have been reviewed recently, concluding that evidence so far shows varied and mostly limited effects [93]. However, a placebo-controlled evaluation of single oral administration of 0.1 g/kg Tau before resistance training did observe a significant positive effect on exercise performance [94], and a meta-analysis of ten published studies concluded that Tau supplements of 1 to 6 g/day for 2 weeks did improve endurance performance [95]. Overall, Tau supplementation was well tolerated, as no severe adverse events have been reported.…”
Section: Adverse Effects and Human Clinical Trialsmentioning
confidence: 99%
“…In healthy subjects, benefits of Tau supplementation on aerobic and anaerobic performance, muscle damage, metabolic stress, and recovery have been reviewed recently, concluding that evidence so far shows varied and mostly limited effects [93]. However, a placebo-controlled evaluation of single oral administration of 0.1 g/kg Tau before resistance training did observe a significant positive effect on exercise performance [94], and a meta-analysis of ten published studies concluded that Tau supplements of 1 to 6 g/day for 2 weeks did improve endurance performance [95]. Overall, Tau supplementation was well tolerated, as no severe adverse events have been reported.…”
Section: Adverse Effects and Human Clinical Trialsmentioning
confidence: 99%
“…Muscle fatigue is the inability of a muscle or group of muscles to produce the required static force or mechanical power within a set time, or the inability to perform the total amount of work under certain conditions 17 . The development of muscle fatigue is determined among others by the availability of energy substrates and the accumulation of products of their metabolism 18 20 . Muscle work requires the intensification of various processes in muscle cells to meet the high demand for ATP.…”
Section: Introductionmentioning
confidence: 99%